Reconstrução paleoambiental com base em sementes (semi-fósseis) na área de proteção ambiental das ilhas e várzeas do rio Paraná, Brasil. - Ramírez, Alma Isbel Ariza (2014)
The floodplain of the Upper Paraná River is studied in the last stretch of the Paraná River in Brazil, where still there is an ecosystem with river-floodplain interaction, the flood pulse is considered the main factor that regulates the communities? structure and the functioning of this ecosystem. Although changed by the operation of the hydroelectric plants reservoirs upstream, the hydro-sedimentological cycles still respect certain seasonality. The present environments in the formation process of the islands propitiate different conditions for the deployment of vegetation and accumulation of seeds. The project evaluated if the acting hydro-sedimentary processes in a neo-tropical floodplain influence the composition of the vegetation structure through semi-fossils seeds preserved in sediments of three islands of the multichannel stretch of the Paraná River and if there is a connection between the vegetation change in the last 50 years with the natural changes (Niño and Niña phenomenon), and with the anthropogenic alterations (dams), using semi-fossil seeds as paleo-bioindicators. Through facies analysis of sediments sampled by the following environmental succession: Mutum Island: an open channel, which becomes "ressaco", lake reaching the current conditions of the swap; Floresta Island: the same sequence of previous island but over the terrestrial environment and in the Bandeirantes island with a very different sequence indicating the development of floodplain. In the deposits of the Mutum Island were collected 2826 seeds of 26 families and 34 genders, while on the Floresta Island were 319 seeds of 37 families and 40 genders. In the Bandeirantes Island were identified 1204 seeds belonging to 43 families and 43 genders. The variation in the types of seeds from the base to the top of the sedimentary column shows that the vegetation changes according with the affected environmental conditions and that the seeds have great potential as "proxy" in river systems. The analysis of the hydrological cycle over the past 50 years for the Paraná and Baia subsystem and Ivinhema subsystem, allowed us to prove that besides of the natural processes, the anthropogenic processes are influencing the composition of vegetation.